MEDICAL TOURISM MARKET AND INTER-STAKEHOLDERS' RELATIONS IN TURKEY: A COMPARATIVE INVESTIGATION FROM REVERSE INNOVATION AND DESTINATION GOVERNANCE VIEWPOINT - Armando Aliu; Hakki Cilginoglu; Ömer Özkan; Dorian Aliu (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study aims to analyze inter-stakeholders' interactions, destination governance, reverse innovation and the tasks of central government within Turkish medical tourism market. The investigation's objective is to shed lights on scientists and practitioners regarding to what extent medical tourism is affected by stakeholders. Likewise, the originality of this investigation is that this study is the first attempt that links up reverse innovation and stakeholder approach as a holistic strategy and competitive advantage tool in medical tourism. The statistical evidences of Turkey also support the fact that the incline of medical tourism incomes and benefits is tightly bound on key inter-stakeholders' collaborations, marketing tools, specific strategies, effective governance mechanism and cooperation with civil society organizations. This study is a thematic case that comprises particular research fields and formulates advanced arguments that are embedded in enriched relevant literature review and the highlights of the 7th International Health Tourism Congress. – – Bu calismanin amaci; Türk medikal turizm piyasasinda merkezi yönetimin görevleri, tersine inovasyon, destinasyon yönetisimi ve paydaslar arasi etkilesimleri analiz etmektir. Arastırmanin hedefi; bilim insanlarina ve sektördeki profesyonellere / uygulayicilara medikal turizmin paydaslar tarafindan ne dereceye kadar etkilendigi hakkinda isik tutmaktir. Ayrica, bu arastirmanin özgünlügü medikal turizmde rekabet avantaji araci ve bütünsel strateji olarak paydas yaklasimi ile tersine inovasyon arasinda baglanti kuran ilk girisim olmasidir. Türkiye'nin istatistiksel verileri de medikal turizmdeki yükselis trendinin ve faydalarinin sivil toplum kuruluslari ile isbirligi, efektif yönetisim mekanizmasi, spesifik stratejiler, pazarlama araclari ve kilit paydaslar arasi isbirliklerine sikica bagli oldugunu desteklemektedir. Bu calisma tematik bir örnek olay olup, 7. Uluslararasi Saglik Turizmi Kongresi'nde vurgulanan hususlar ile iliskilendirilmis literatür taramasina dayali olarak formüle edilmis gelismis argümanlar ve spesifik arastirma alanlarini icermektedir.
Conference: 7th International Health Tourism Congress, 18-21st November 2015, Istanbul / Turkey; Additional information: The authors are grateful to the Republic of Turkey Ministry of Health for supporting them by means of sharing the 2013-2014 statistical datasets. Likewise, they are indebted to the Organizing Committee of the 7th International Health Tourism Congress for their collaboration. Furthermore, the authors would like to express their sincere thanks to Istanbul Commerce University for ensuring them institutional opportunities. A previous version of this research was presented as a proceeding at the 7th International Health Tourism Congress which is organized every year by Health Tourism Association of Turkey. The congress was held on 18-21st November 2015 in Silence Istanbul Hotel & Convention Center (Istanbul / TURKEY). Likewise, this investigation was written in the framework of a large-scale practical research project (Project Code: ICU-DUPA/2015-EUP-01) that is conducted at Istanbul Commerce University, Research and Project Development Academy (DUPA).
Keywords: F63; H51; I11; I15; I18; M38; 330; Medical Tourism; Reverse Innovation; Stakeholders; Collaboration; Destination Governance